PERSEPSI GURU SMA TERHADAP ISU PENGADAAN UJIAN NASIONAL - Siti Enik Mukhoiyaroh Bambang; Adit Trinaldi; Sophia Rahmawati; Wahdaniah; Lusia Oktri Wini (Jurnal Ilmiah Bina Edukasi, 2025)
This research aims to describe high school teachers' perceptions of the issue of administering the National Examination. The research method uses a qualitative research type with a phenomenological approach. Research data were obtained through observation and interviews related to the National Examination phenomenon. Research participants used purposive sampling consisting of nine high school teachers in various generations, namely generation x, generation y, and generation z in Batanghari Regency. The validity of the data used is source triangulation through Miles and Huberman's theory. The results of the study indicate that high school teachers of generations X, Y, and Z in Batanghari Regency agree to hold the National Examination by reviewing student graduation indicators, using technology in its implementation, and can improve learning motivation and student character.